2017
DOI: 10.1097/grf.0000000000000252
|View full text |Cite
|
Sign up to set email alerts
|

Low–Molecular-Weight Heparin for the Prevention of Placenta-mediated Pregnancy Complications

Abstract: During the past decade, prophylactic doses of low-molecular-weight heparin (LMWH) have been suggested to decrease the risk of placental-mediated complications. Herein, we review the prospective randomized trials that addressed the usefulness of LMWH in preventing placental-mediated complications in high-risk women. Inclusion criteria and results of these trials are heterogeneous. Unlike older trials (3 of 4 are single center), recent trials (all are multicenter) do not show beneficial effect of LMWH. There is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…As far as the combination's safety is concerned, significant bleeding, related to obstetrical reasons, allergic skin reactions, thrombocytopenia, and osteoporotic fractures are reported. 85 In particular, for osteoporosis, Laskin et al reported a mean change in bone mineral density at the lumbar spine and the femoral neck which did not differ significantly between LMWH and aspirin, and aspirin alone treatment groups. 51 The incidence of thrombocytopenia is not significant.…”
Section: Other Studiesmentioning
confidence: 98%
See 3 more Smart Citations
“…As far as the combination's safety is concerned, significant bleeding, related to obstetrical reasons, allergic skin reactions, thrombocytopenia, and osteoporotic fractures are reported. 85 In particular, for osteoporosis, Laskin et al reported a mean change in bone mineral density at the lumbar spine and the femoral neck which did not differ significantly between LMWH and aspirin, and aspirin alone treatment groups. 51 The incidence of thrombocytopenia is not significant.…”
Section: Other Studiesmentioning
confidence: 98%
“…without Aspirin can be beneficial for pregnancy-related complications in general (Grandone et al) 86 . However, the addition of LMWH needs to be further researched to evaluate its actual effectiveness in placental-mediated diseases (Haddad et al) 87 . An older Cochrane systematic review assessed similar outcomes.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…Strong evidence links thrombophilia to adverse pregnancy outcomes [3,4]. The effects of low molecular weight heparin (LMWH) on hereditary thrombophilia and obstetric problems are a subject of debate [5][6][7]). Twin pregnancies raise the risk of blood clotting and thromboembolism, especially when assisted reproductive technology (ART) leads to higher levels of oestrogen and progesterone, thus elevating the risk of blood clots in subsequent twin pregnancies.…”
Section: Introductionmentioning
confidence: 99%